2019
DOI: 10.1039/c9ra05995d
|View full text |Cite
|
Sign up to set email alerts
|

A single-phase white light emitting phosphor Ba3Y(PO4)3:Ce3+/Tb3+/Mn2+: luminescence, energy transfer and thermal stability

Abstract: A series of Ce3+/Tb3+, Tb3+/Mn2+ and Ce3+/Tb3+/Mn2+ doped Ba3Y(PO4)3 were synthesized by the high temperature solid state method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…A maximum Ce 3+ / Tb 3+ energy transfer efficiency of 91% was obtained for NZPO:0.05Ce 3+ /0.08Tb 3+ sample which is found to be higher than that of the similar reported orthophosphate phosphors, such as NaBaPO 4 :0.04Ce 3+ / 0.15Tb 3+ (78.8%), 43 NaCaPO 4 0.02 Ce 3+ /0.12Tb 3+ (80%), 44 Ba 3 -Y(PO 4 ) 3 :0.05Ce 3+ /0.45 Tb 3+ (69.9%). 45 Generally, two factors can be responsible for the resonant energy transfer mechanism: the exchange interaction and the multipolar interaction.…”
Section: Luminescence Nzpo:tb 3+ Phosphorsmentioning
confidence: 99%
“…A maximum Ce 3+ / Tb 3+ energy transfer efficiency of 91% was obtained for NZPO:0.05Ce 3+ /0.08Tb 3+ sample which is found to be higher than that of the similar reported orthophosphate phosphors, such as NaBaPO 4 :0.04Ce 3+ / 0.15Tb 3+ (78.8%), 43 NaCaPO 4 0.02 Ce 3+ /0.12Tb 3+ (80%), 44 Ba 3 -Y(PO 4 ) 3 :0.05Ce 3+ /0.45 Tb 3+ (69.9%). 45 Generally, two factors can be responsible for the resonant energy transfer mechanism: the exchange interaction and the multipolar interaction.…”
Section: Luminescence Nzpo:tb 3+ Phosphorsmentioning
confidence: 99%
“…[ 20 ] Y Chen and colleagues reported a Ba 3 Y(PO 4 ) 3 :Ce 3+ /Tb 3+ /Mn 2+ phosphor for warm white LED applications. [ 21 ] In addition to this, the luminescence behaviour of Pr 3+ ions varied strongly in different hosts and provided red, green, and blue emissions with respect to the various host matrices. To the best of our knowledge Ba 3 Y(PO 4 ) 3 doped with Pr 3+ ions has not been reported, so in this work we studied the synthesis and luminescence properties of a Pr 3+ ion‐doped Ba 3 Y(PO 4 ) 3 phosphor.…”
Section: Introductionmentioning
confidence: 98%
“…In the last few years, a large number of studies based on the BYP matrix have focused on the tunable visible phosphors doped with rare-earth ions like Eu 3+ , Dy 3+ , Sm 3+ , etc., or temperature-sensing phosphors with Ce 3+ /Eu 2+ /Mn 2+ , Ce 3+ /Tb 3+ , Tb 3+ /Eu 3+ ions, etc. [21][22][23][24][25][26]. Y. Takebuchi et al have reported that the Ba 3 RE(PO 4 ) 3 (RE = Y, La and Lu) crystals showed the intrinsic luminescence peaked at 400 nm under vacuum-UV and X-ray excitation; the X-ray-induced scintillation decay time was several microseconds, and the absolute light yields were estimated to be 960, 1160, and 1220 ph/5.5 MeV under 241 Am α-ray irradiation, respectively [27].…”
Section: Introductionmentioning
confidence: 99%